IJIN PENDIRIAN RUMAH SAKIT OLEH MODAL ASING BERKAITAN DENGAN PENGGUNAAN BAHASA ASING DALAM PENAMAAN RUMAH SAKIT - Diantari, Ayu Prilia (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 1 (2014)DO - 10.24843/JMHU.2014.v03.i01.p04, 2014)
The establishment of the hospital takes no small amount of capital and therefore the establishment of the hospital does not relu out the possibility of the cooperation between foreign investors with local investors, the establishment of hospital procedures by foreign investors is regulated in health minister 147/MENKES/PER/2010 about the hospital licensing. The parties will establish a hospital must comply with the regulations contained in the articles of ministerial regulation 147/MENKES/PER/2010. Regulation of the minister of healty in the attachment 147/MENKES/PER/2010 number 6 mentioned for naming the hospital may not use language/foreign terms such as : “an international, world-class, global, but the reality in Bali and more hospital are using language/foreign terms in the naming of the hospital.
Keywords: hospital, licensing, foreign term